Parameter Sensitivity Analysis of Permanent Magnetic Eddy-current Flexible Transmission - Tongyu Shi (Jixie chuandong)
To study the effect of the parameters of permanent magnet eddy-current flexible transmission on multiple performance objectives of output performance， the accurate analytical model is built. By using the method of separation of variables， the output performance under different parameters is calculated， the accuracy of the model of permanent magnet eddy-current flexible transmission is verified by using the finite element simulation software ANSOFT. After that， the sensitivity of the different parameters to multi-objective optimization is analyzed， and the main parameters of multi-objective optimization design are determined. The results show that， the analytical model of permanent magnetic eddy-current flexible transmission is very accurate. After analysis， it is shown that different parameters have different effects on output performance. It has a good reference for preliminary design and optimization design.